1998
DOI: 10.1007/s004390050711
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric length and telomerase activity vary with age in peripheral blood cells obtained from normal individuals

Abstract: The telomerase activity and length of telomeres of peripheral blood mononuclear cells obtained from 124 healthy individuals aged 4-95 years was measured. Telomerase activity level was semiquantitatively assessed by a fluorescent-telomeric repeat amplification protocol (fluorescent-TRAP) using an internal telomerase assay standard, fluorescent primers and an automated laser fluorescent DNA sequencer. Telomeric length, measured by assay of terminal restriction fragments (TRFs), was determined in HinfI-digested D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
160
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(179 citation statements)
references
References 32 publications
15
160
3
1
Order By: Relevance
“…Telomerase activity was undetected in the majority of donor CD4 ϩ (75%) and CD8 ϩ (83%) T cells and B (91%) cell populations. Low levels of telomerase activity were detected in some donors and did not appear to be restricted to the young donors as previously reported (18) or to either gender (Fig. 2).…”
Section: Telomerase Expression In Peripheral Blood Cd4 ϩ and Cd8 ϩ T supporting
confidence: 81%
See 4 more Smart Citations
“…Telomerase activity was undetected in the majority of donor CD4 ϩ (75%) and CD8 ϩ (83%) T cells and B (91%) cell populations. Low levels of telomerase activity were detected in some donors and did not appear to be restricted to the young donors as previously reported (18) or to either gender (Fig. 2).…”
Section: Telomerase Expression In Peripheral Blood Cd4 ϩ and Cd8 ϩ T supporting
confidence: 81%
“…Age influence on telomerase activity in PBMC has been reported recently (18). It was found that telomerase activity in freshly isolated PBMC markedly declined from newborn to adolescence and was stable at low to undetectable levels in all adult life (18). Because PBMC consist of multiple cell lineages, such differences in telomerase activity may reflect changes such as decreased numbers of telomeraseexpressing stem cells and naive T cells newly derived from the thymus.…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations